A question of identity: social, political, and historical aspects of identity dynamics in Jewish and other contexts - Katz, Dikla Rivlin; Hacham, Noah; Herman, Geoffrey; Sagiv, Lilach (De Gruyter Oldenbourg, 2019)
Frontmatter -- Preface -- Contents -- A question of identity: Introduction / Sagiv, Lilach / Katz, Dikla Rivlin / Hacham, Noah / Herman, Geoffrey -- Part I: Ancient Mesopotamia and Further East -- 1. In His Majesty’s Service / Zilberg, Peter -- 2. Judean Identity during the Exile / Bloch, Yigal -- 3. Issues in the Historical Geography and the Ethno-Linguistic Character of the Zagros and Adjacent Regions / Zadok, Ran -- 4. Going West / Kiperwasser, Reuven -- 5. Jewish Identity in Babylonia in the Period of the Incantation Bowls / Herman, Geoffrey -- 6. The Quest of the Historical Metatron: Enoch or Jesus / Boyarin, Daniel -- Part II: The Hellenistic and Roman World -- 7. Priests in Exile / Piotrkowski, Meron M. -- 8. Iron Wall or Common Feast? / Hacham, Noah / Sagiv, Lilach -- 9. Ptolemy II Philadelphus in the Letter of Aristeas §§1–27 / Pearce, Sarah -- 10. Literary Genres and Identity in the Letter of Aristeas / Honigman, Sylvie -- 11. Monotheism as an Identity Norm / Sterling, Gregory E. -- 12. Material Culture and Ethnic Identity in Hellenistic-Period Galilee / Leibner, Uzi -- 13. “How Fine are the Works of this People”? / Silberklang, Hillel -- Part III: Religious and National Identities in a Complex World -- 14. The Context of Conversions in Early Modern Europe / Kaplan, Benjamin J. -- 15. So What’s Really in a Name? Theology of Etymology in Sixteenth-Century Arian Thought / Luszczynska, Magdalena -- 16. “It’s All Hebrew to Me” / Shafir, Gershon -- 17. Social and Spatial Borders between “Us” and “Them” / Katz, Dikla Rivlin -- Contributors -- Index